Breastmilk Is a Novel Source of Stem Cells with Multilineage Differentiation Potential123. (20th September 2012) - Hassiotou, Foteini; Beltran, Adriana; Chetwynd, Ellen; Stuebe, Alison M.; Twigger, Alecia‐Jane; Metzger, Philipp; Trengove, Naomi; Lai, Ching Tat; Filgueira, Luis; Blancafort, Pilar; Hartmann, Peter E.
Abstract: The mammary gland undergoes significant remodeling during pregnancy and lactation, which is fuelled by controlled mammary stem cell (MaSC) proliferation. The scarcity of human lactating breast tissue specimens and the low numbers and quiescent state of MaSCs in the resting breast have hindered understanding of both normal MaSC dynamics and the molecular determinants that drive their aberrant self‐renewal in breast cancer. Here, we demonstrate that human breastmilk contains stem cells (hBSCs) with multilineage properties. Breastmilk cells from different donors displayed variable expression of pluripotency genes normally found in human embryonic stem cells (hESCs). These genes included the transcription factors (TFs) OCT4, SOX2, NANOG, known to constitute the core self‐renewal circuitry of hESCs. When cultured in the presence of mouse embryonic feeder fibroblasts, a population of hBSCs exhibited an encapsulated ESC‐like colony morphology and phenotype and could be passaged in secondary and tertiary clonogenic cultures. While self‐renewal TFs were found silenced in the normal resting epithelium, they were dramatically upregulated in breastmilk cells cultured in 3D spheroid conditions. Furthermore, hBSCs differentiated in vitro into cell lineages from all three germ layers. These findings provide evidence that breastmilk represents a novel and noninvasive source of patient‐specific stem cells with multilineage potential and establish a method for expansion of these cells in culture. They also highlight the potential of these cells to be used as novel models to understand adult stem cell plasticity and breast cancer, with potential use in bioengineering and tissue regeneration. STEM Cells 2012;30:2164–2174